Multiple Cause of Death, 1995 ([Verlag nicht ermittelbar], 1998)
This data collection presents information about the causes of all recorded deaths occurring in the United States, Puerto Rico, the Virgin Islands, and Guam during 1995. Data are provided concerning underlying causes of death, multiple conditions that caused the death, place of death, residence of the deceased (e.g., region, division, state, county), whether an autopsy was performed, and the month and day of the week of the death. In addition, data are supplied on the sex, race, age, marital status, education, usual occupation, and origin or descent of the deceased. Along with the Combined Territories Public Use file, a subset based on state of occurrence has been created for Puerto Rico, Virgin Islands and Guam. Mortality detail data for 1995 also can be extracted from this file. The mortality detail records are contained in the first 159 positions of these multiple cause records. The multiple cause of death fields were coded from the MANUAL OF THE INTERNATIONAL STATISTICAL CLASSIFICATION OF DISEASES, INJURIES, AND CAUSE-OF-DEATH, NINTH REVISION (ICD-9), VOLUMES 1 AND 2.